Kebijakan Moderasi Beragama di Indonesia - M. Munif; Mujamil Qomar; ABD AZIZ (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This study purpose is describe the policy of religious moderation in Indonesia includes strengths, weaknesses, opportunities and challenges. This research uses qualitative research with the type of library research (library research). The data collection by collecting literature related to the research topic, using content analysis. The research results are : Religious moderation is a way of understanding and practising moderate religion and religion by prioritizing the principles of tolerance, inclusiveness and accommodativeness and upholding the constitution of the nation and state. The principles of religious moderation are national commitment, toleration, anti-radicalism and violence, and accommodation of local culture. The government in the religious moderation policy program has things, first: advantages are increasing tolerance; reject acts of violence in the name of religion; strengthening national commitments and encouraging the perspectives, attitudes, and practices of a middle way (moderate) religion; second: weaknesses are lack of understanding and awareness of the community; there are still acts of intolerance, discrimination, and violence; weak law enforcement and low quality of religious education; third: opportunities are support from the central and regional governments; there is cooperation and coordination between the Ministry of Religion and various related institutions and organizations; there is a road map for the implementation of religious moderation and there is awareness and participation of civil society; fourth: challenges are claims of truth; there is a religion understanding that is not in line with the national commitment of the Unitary State of the Republic of Indonesia; there are acts of violence committed in the name of religion and the influence of globalization and information technology.